2020
DOI: 10.1002/alr.22484
|View full text |Cite
|
Sign up to set email alerts
|

Inverted papilloma is associated with greater radiographic inflammatory disease than other sinonasal malignancy

Abstract: Background The pathogenesis of inverted papilloma (IP) has not been fully elucidated. However, chronic paranasal sinus inflammation has been anecdotally observed in sites distant from tumor obstruction in IP patients, suggesting an association between inflammation and IP tumorigenesis. This study assesses the association between sinonasal inflammation found in IP and compares this to the level of inflammation observed in other sinonasal tumors. Methods A retrospective chart review was performed identifying pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…The data show an association between IPs and contralateral sinusitis (58.9% vs. 26.7%), 31 while case–control studies reveal that organic solvents may be risk factors in IP development (OR 2.11). 32 The evidence around industrial exposures is contradictory.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The data show an association between IPs and contralateral sinusitis (58.9% vs. 26.7%), 31 while case–control studies reveal that organic solvents may be risk factors in IP development (OR 2.11). 32 The evidence around industrial exposures is contradictory.…”
Section: Discussionmentioning
confidence: 89%
“…They cited the Orlandi study as a possible role of inflammation in the development of IP, but also emphasized there was limited evidence to support the theory. An updated, 2020 retrospective cohort study by Papagiannopoulous et al 31 replicated these results, comparing CT scans to determine contralateral sinus inflammation in patient with unilateral IP. They found that IP patients had a higher prevalence of contralateral sinusitis than the control group (58.9% vs. 26.7%) with higher Lund‐McKay scores in IP patients than controls (1.9 vs. 0.26).…”
Section: Chronic Sinonasal Inflammation: Environmental and Occupation...mentioning
confidence: 90%
“…Такого же мнения придерживается ряд авторов, предположивших, что инвертированные папилломы возникают на фоне хронического воспалительного процесса [19]. Так, было показано, что пациенты с односторонним распространением инвертированной папилломы имели более выраженный контрлатеральный синусит в сравнении с группой пациентов без инвертированной папилломы [20].…”
Section: Discussionunclassified
“…[20] Nazal mukozadaki bu neoplastik büyümeyi ve metaplaziyi açıklayacak sigara kullanımı, mesleksel ve endüstriyel maruziyetler, HPV, kronik enf lamasyon gibi çeşitli faktörler İP etiyolojisinde araştırılmıştır. [5,[21][22][23] Tüm bu etiyolojik faktörler her iki nazal kaviteyi aynı anda etkilemektedir. İnverted papillomun %96-98 oranlarında tek taraflı görüldüğü bilinmektedir.…”
Section: Discussionunclassified